BUKU SAKU BERBASIS MOBILE BAGI ORANG TUA DENGAN ANAK PJB - Yosefina Oktaviani Santoso; Arcelina Sukiatmodjo; Daniel Adrian Setiady; Shinta Estri Wahyuningrum; Dwi Setianto (PROSIDING SNAST, 2018)
Congenital Heart Disease(CHD) is an abnormality of the structure and function of the heart circulation that occurs since the pregnancy.This disease has a very high risk and suffered 8 out of 1000 babies born.The high risk of this disease is not rateable with existing facilities.One of efforts that can be done to overcome the existing problems is to take advantage of technological progress.Electronic Pocket Book for PJB is the result of technology utilization for PJB problem.This Pocketbook-based mobile phone is more flexible,concise,as a reminder and can also be used to store data in the form of images and files.All the features are also the result of interviews with pediatric consultants child heart and 10 parents who have children with PJB. The features available in this application are medical records from doctors,daily needs records of children,daily medication reminders and immunizations,and growth charts of children. This app uses the SCRUM method in its creation and has been tested for safety.In the testing there are two variables of comparison to test the efficiency.This application can be one alternative to solve the existing problems and help deal with the difficulties that have been faced by doctors and parents of children PJB.